2022
DOI: 10.1071/hc22037
|View full text |Cite
|
Sign up to set email alerts
|

Assessing need for primary care services: analysis of New Zealand Health Survey data

Abstract: Introduction. The 2001 Primary Health Care Strategy provided significant new government funding for primary care (general practice and related services) via capitation funding formulas. However, there remain important unanswered questions about how capitation funding formulas should be redesigned to ensure equitable and sustainable service provision to all population groups. Aim. To compare levels of chronic illness, utilisation, and unmet need in patients categorised as 'high-need' with those categorised as n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…We also know that the effects of the COVID-19 pandemic linger in general practice through the effects of delayed presentation, interrupted treatments, increases in demand from those who had COVID-19 and who want more care and increases in demands for mental health consultations, adding to the work of primary care providers. 19,20…”
Section: Prevalence and Persistencymentioning
confidence: 99%
See 2 more Smart Citations
“…We also know that the effects of the COVID-19 pandemic linger in general practice through the effects of delayed presentation, interrupted treatments, increases in demand from those who had COVID-19 and who want more care and increases in demands for mental health consultations, adding to the work of primary care providers. 19,20…”
Section: Prevalence and Persistencymentioning
confidence: 99%
“…VLCA and lower fees practices may need to keep their books open to remain financially sustainable, particularly as a result of the extra financial pressures in practices serving patients with high needs. 20,23 These findings underscore the need to carefully monitor healthcare access disparities, especially during times of healthcare reforms, to avoid unintentionally exacerbating inequities.…”
Section: Populations and Practices Most Affectedmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the New Zealand Health Survey, 5 Hau and colleagues have shown that 'high needs' patients are likely to suffer from multimorbidity, require seven or more GP visits per year, and report barriers to access. 6 On a very similar note, Dowell and colleagues have used routinely collected primary care data to demonstrate that health risk factors and co-morbidities are clustered in a small number of practices with many 'high needs' patients. Considerable challenges, but also opportunities, are afforded to general practice by both the COVID-19 pandemic and the health reforms.…”
Section: From the Editors: Challenges And Opportunities For Sustainab...mentioning
confidence: 99%
“…Māori health providers have been under-funded since their inception [ 4 ], although the majority of Māori (and Pasifika) patients are enrolled in ‘traditional’ (GP-led and owned) practices [ 32 ], and the under-funded nature extends across the primary healthcare sector. This underfunding is particularly evident for those providers that care for high-needs populations (which includes Māori and Pasifika patients) [ 32 34 ]. Evidence has been submitted to Wai 2575 to quantify the direct under-funding so to inform compensation discussions and the cost of the inequality caused by lack of access to primary care services for Māori [ 35 ].…”
mentioning
confidence: 99%